Career Adjustment: Understanding Transitional Challenges Among Newly-Hired Public School Teachers - Flores, Neo Austein V. (International Journal on Integrated Education, 2025)
The study titled “Career Adjustment: Understanding the Transitional Challenges Among Newly-Hired Public School Teachers” explores the lived experiences of newly hired public elementary school teachers during their first year of service, aiming to understand the challenges they face and the coping strategies they employ. Conducted in Cabuyao City, Laguna during School Year 2024–2025, the research provides localized insights into the transitional experiences of new educators in public elementary schools. Using a qualitative phenomenological research design, data were gathered through semi-structured, in-depth interviews with ten purposively selected participants all with one year or less of teaching experience. Colaizzi’s method of phenomenological analysis was used to extract significant statements, formulate meanings, and identify emerging themes. Findings revealed several transitional challenges, including managing large class sizes, addressing diverse learner needs, handling absenteeism and underperformance, and balancing teaching with administrative tasks. The absence of structured orientation and mentoring programs contributed to feelings of unpreparedness, emotional stress, and low self-confidence. Financial constraints and limited teaching resources also increased the burden. To cope, participants sought mentorship from experienced colleagues, engaged in professional development, applied differentiated instruction, and cultivated supportive relationships within the school community. They also practiced emotional resilience, time management, and stress-reduction strategies to navigate their adjustment period. The study recommends the implementation of a Transition Support Program - a structured, context-responsive initiative to assist newly hired teachers in adapting to public-school teaching demands. This program should encourage collaboration among school administrators, policymakers, and educators to build a supportive and sustainable teaching environment. Overall, the study offers valuable insights for improving teacher induction programs and enhancing retention strategies in the Philippine public education system, highlighting the importance of supporting novice teachers during their critical first year.